The Efficacy and Safety of Semaglutide-Based Medications for Long-Term Weight Loss and Cardiovascular Health: Semaglutide for Weight Loss and Cardiovascular Health - Khalid, Sadaf; Malik, Maha Areej; Khan, Muhammad Noman Ul Haq; Khan, Muhammad Usama; Sultan, Habib; Noor, Danish (Pakistan Journal of Health Sciences, 2025)
The advantages of semaglutide associated with weight loss have been well documented. However, its utilization regarding clinical safety and efficacy in treating obesity and Cardiovascular Health (CVH) conditions is less described. Objective: To focus on evaluating the effectiveness and safety of semaglutide-based medications for long-term weight loss and CVH. Methods: PubMed, Google Scholar, Cochrane Library, Scopus, and Clinical Trial. Gov. was systematically explored to undertake a detailed search of relevant papers from January 2015 to February 2024. Following PRISMA guidelines 1500 papers were identified initially, of which 500 papers were screened for their titles and abstracts, leading to a screening of eligibility of 200 full-text papers. Finally, 22 studies were further evaluated based on inclusion, and exclusion criteria, relevant data was gathered, and a systematic review was performed. Results: The results highlight the substantial contribution of semaglutide to clinically meaningful weight reduction among individuals with obesity. Overweight participants with semaglutide compared to other AOMs showed improved clinical efficacy and safety for sustainable weight loss, healthy BMI, and CV-related factors such as improvements in blood pressure, lipid profile, and risk factors. Conclusions: Semaglutide-based medicines not only are safe in clinical terms, but also work well for people with obesity, assisting them to reduce their weight in the long term while enhancing conditions of cardiovascular health. Results show benefits in terms of BMI, BP and lipid profiles thereby indicating that semaglutide may serve as a valuable, sustainable intervention for managing obesity and associated cardiovascular risks.